PENGARUH KEPRIBADIAN ULUL ALBAB TERHADAP KEMAMPUAN MENGHADAPI TANTANGAN - Rahmat Aziz, M.Si (lp2m-uin malang, 2007)
The purpose of this study was to study the impact of ulul albab personality on the adversity quotient. The sample was composed of 139 undergraduate of Islamic State University of Malang. The result showed that r=0.182 p=0.045 it means ulul albab personality influence of adversity quotient. Key word: Ulul Albab Personality, Adversity Quotient